Age impairs mnemonic discrimination of objects more than scenes: A web-based, large-scale approach across the lifespan. (April 2021) - Güsten, Jeremie; Ziegler, Gabriel; Düzel, Emrah; Berron, David
Abstract: Recent findings suggest that the effect of aging on recognition memory is modality-dependent, affecting memory for objects and scenes differently. However, the lifespan trajectory of memory decline in these domains remains unclear. A major challenge for assessing domain-specific trajectories is the need to utilize different types of stimuli for each domain (objects and scenes). We tested the large sample required to cover much of the adult lifespan using a large stimulus range via web-based assessments. 1554 participants (18–77 years) performed an online mnemonic discrimination task, tested on a pool of 2708 stimuli (Berron et al., 2018). Using corrected hit-rate ( Pr ) as a measure of performance, we show age-related decline in mnemonic discrimination in both domains, notably with a stronger decline in object memory, driven by a linear increase in the false recognition rate with advancing age. These data are the first to identify a linear age-related decline in mnemonic discrimination and a stronger, linear trajectory of decline in the object domain. Our data can inform basic and clinical memory research on the effects of aging on memory and help advancing the implementation of digital cognitive research tools.